Sociological Implications of Cancer Treatment on Individuals and Communities (Journal of Management and Social Sciences, 2024)
Cancer, marked by the uncontrolled proliferation of abnormal cells leading to the destruction of healthy tissue, remains a formidable global health challenge. While advances in cancer screening, therapy, and prevention have contributed to improvedsurvival rates, the progress has been unequal across the world, particularly in developing countries like Nigeria. This discrepancy is exacerbated by a complex web of factors, including inadequate funding, weak policy execution, and a lack of political will and dedication, resulting in persistently high cancer rates in Nigeria. Using a qualitative approach, this paper relies on secondary data from academic journals and online articles. The findings of this study reveal a disheartening reality: a significant portion of cancer patients in Nigeria continue to face the dire challenge of delayed and ineffective diagnosis and treatment. Furthermore, cancer, as a complex and varied disease, necessitates a range of therapies, including surgery, radiation, and systemic treatments such as chemotherapy, hormonal therapy, and biological therapies. The choice of therapy is intricately tied to the type of cancer and the individual patient, shaping treatment plans, procedural considerations, and expected therapeutic responses. Equally significant is the recognition that cancer's impact transcends the individual patient, affecting their relationships, communities, and social networks. The relatives and loved ones of cancer patients bear the physical, social, and emotional burden of cancer diagnosis, treatment, and recovery, reinforcing the importance of holistic care and support systems. In light of these findings, healthcare professionals and decision-makers should actively encourage public participation in the support for cancer patients. The public perception of cancer and its impact on individuals and families must be transformed, dispelling stigma and fostering empathy. Media campaigns, public awareness pamphlets, and educational initiatives can play a pivotal role in achieving this goal.